Justifying Work: Occupational Rhetorics as Resources in Restaurant Kitchens - Fine, Gary Alan (Administrative Science Quarterly, 1996)
Occupational rhetoric has been referred to elsewhere, generally with less emphasis on self-identity, as ideology. Those who speak of occupational ideology typically refer to a worldview or coherent perspective, learned through socialization, that articulates the relationship between the occupation and other types of work. Occupations often have been defined as belonging to a particular class of work, linked to a single occupational rhetoric. In contrast, I argue here that most occupations are segmented in terms of divisions among workers, among work tasks, and among occupational identities. I present evidence from an ethnographic study of restaurant cooks to demonstrate that workers rely on a variety of occupational rhetorics as resources to define their work and their identity. I claim that cooks draw on the alternative rhetorics of profession, art, business, and labor to shape how they think of themselves as workers. The paper shows that occupational identity is socially, temporally, and spatially situated, raising the question of when particular rhetorical strategies will be relied upon.*